Metric Approach to Anticipate Reusability of Object-Oriented (O-O) Software Systems - Dr Parul Gandhi, Bharti Bisht, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to meet the fast software evolution, there is a call for the work on software development based process by reducing time as well as efforts. The aim of the development process should not only be developing software products and services but also focus on improving the quality of the particular software. Software Reusability can be considered as one of the solutions to achieve both objectives i.e. productivity as well as quality. There has been an evolution of various methods and techniques related to construction of reusable components over many years. Object-oriented approach also assures increased software reusability. It is easier to reuse object-oriented software rather than conventional software. The notion of reusability related to Object-oriented software can be achieved through inheritance which in turn contributes to development of reusable components. In this paper different metrics related to software reusability of Object-oriented software systems has been summarized and evaluated using Python. Three python-based programs are considered as datasets for this study-the first dataset depicts single-level inheritance, the second dataset depicts hierarchical inheritance whereas the third dataset depicts multilevel inheritance. This study shows more impact of multilevel inheritance on the reusability of Object-oriented software systems and also helped to understand the important role of metrics in evaluation of object-oriented systems.